Analysis of microRNA-transcript regulatory networks in the hippocampus of the BTBR mouse model of autism - Gasparini, Silvia; Licursi, Valerio; Rinaldi, Arianna; Ricceri, Laura; Scattoni, Maria Luisa; Presutti, Carlo; Mannironi, Cecilia (Frontiers in Cellular Neuroscience, 2025)
Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition with unknown etiology. Currently, the role of post-transcriptional mechanisms in ASD remains unclear. microRNAs (miRNAs) are small non-coding regulatory RNAs that mediate mRNA destabilization and/or translational repression. To investigate the potential role of miRNAs in ASD, we performed miRNA expression profiling in the hippocampus of the BTBR ASD mouse model and age-matched C57BL/6 J mice. Alongside, we analyzed the BTBR hippocampal transcriptomic profile to identify differentially expressed transcripts (DETs). By integrating differentially expressed miRNA (DEmiRNA) and DET lists, we discovered mRNA transcripts that are putative targets of BTBR DEmiRNAs and exhibit an anti-correlated differential expression in the BTBR hippocampus. These interactions suggest potential regulatory networks related to gene transcription regulation, and synaptic structure and function relevant for ASD. These include miR-200 family members, miR-200a-3p, miR-200b-3p, miR-200c-3p, and miR-429, and the experimentally validated target, the transcription factor Zeb2. Moreover, we identified a set of non-canonical interactions characterized by extensive pairing between BTBR DEmiRNAs and DETs, potentially triggering target-directed miRNA degradation (TDMD). Our findings support a role for miRNA dysregulation in the pathophysiology of ASD.